Macromedia Flash 8 Learning Media to Increase Learning Interest in Theme 2 Students Always Save Energy Class IV SD Negeri 016555 Asahan - Wulandari, Vita; Landong, Ahmad (Universitas Trunojoyo Madura, 2022)
This study aims to: (1) develop media using Macromedia Flash 8 applications in elementary thematic learning, (2) determine the feasibility of developing Canva applications in elementary thematic learning. This research is a type of Research and Development (RD) research with the ADDIE model which includes five steps, including: analysis, Design, Development, Implementation, Evaluation . The subjects in this study were media expert validators, material experts, education practitioners, namely fourth grade teachers and fourth grade elementary school students. The research instruments used in data collection were questionnaires, observations, and documentation. The results of this study indicate that the Macromedia Flash 8 Application learning media in the Thematic Learning of the Always Save Energy Theme for Grade IV Elementary School is